The thermal properties of CaO-Nanofluids. (March 2019) - Sunil, J.; Vignesh, J.; Vettumperumal, R.; Maheswaran, R.; Raja, R.A. Arul
Abstract: The poor bio-degradability of mineral lubricant oils pressurizes to develop bio-degradable, renewable, less toxic and evaporative lubricating agents. In this study, the rice bran oil is used as a base fluid and CaO nanoparticles are used as bio-lubricant additive. The CaO nanoparticles are synthesised from chicken egg shells and are characterised by Energy Dispersive X-Ray Spectroscopy (EDS), Scanning Electron Microscope (SEM) and X-Ray Diffraction (XRD). The CaO-nanofluids are formulated by ultrasonication process and their chemical stability and thermal properties are estimated by Thermogravimetric Analysis (TGA) and Differential Thermogravimetric Analysis (DTA) under nitrogen atmosphere and Fourier Transform Infrared Spectroscopy (FTIR). The results designate that the thermal properties of rice bran oil is enhanced by 18.2% and 25% at 0.25 wt% and 0.50 wt% of CaO-nanofluids, respectively. Highlights: The disposal and combustion products of mineral oil are long-term pollution to both aquatic and terrestrial ecosystems. Nanofluids are the alternative for mineral base lubricants. CaO nanoparticles are synthesised from chicken egg shells. Thermal properties of the rice bran oil is increases with increasing CaO nanoparticles concentration. The results show that the rice bran oil is a potential candidate for developing bio-lubricant formulations.